Licochalcone D reduces H2O2-induced SH-SY5Y cell neurotoxicity by regulating reactive oxygen species - Kwak, Ah-Won; Park, Seungmin; Oh, Ha-Na; Shim, Jung-Hyun; Yoon, Goo; Kim, Woo-Keun (Frontiers in Pharmacology, 2025)
Oxidative stress, one of the primary pathogenic factors in neurodegenerative diseases, plays a key role in neuronal damage via various apoptotic mechanisms. Using natural antioxidants to counteract oxidative stress may be a useful approach to slow the progression of neurodegenerative diseases. Licochalcone D (LCD), a root extract of Glycyrrhiza inflata, has various pharmacological activities; nonetheless, its neuroprotective effects and cellular mechanisms against oxidative damage in neuronal cells remain to be elucidated. To address this, we examined the neuroprotective effects and mechanisms of LCD in H2O2-induced cytotoxicity and neurotoxicity in the SH-SY5Y human neuroblastoma cell line. SH-SY5Y human neuroblastoma cells were differentiated using retinoic acid and subsequently treated with LCD and H2O2. Cell viability and cytotoxicity were evaluated using cell counting kit-8 and lactate dehydrogenase assays, respectively. Intracellular reactive oxygen species levels were quantified using 2′,7′-dichlorofluorescein diacetate, while mitochondrial membrane potential was assessed using 5,5′,6,6′-tetrachloro-1,1′,3,3′-tetraethylbenzimidazol-carbocyanine iodide dye. Gene expression analysis was performed by real-time qPCR, and neurite outgrowth was examined using high-content imaging. Protein expression levels were determined by Western blotting. All experiments were conducted in triplicate, and statistical analyses were performed to determine the significance of the results. LCD improved cell viability, reduced reactive oxygen species and lactate dehydrogenase levels, and protected SH-SY5Y cells from oxidative stress. High-content screening confirmed that LCD rescued the oxidative stress-induced inhibition of neurite outgrowth. LCD upregulated the mRNA expression of the neurodevelopmental genes βIII-tubulin, GAP43, Nestin, and MAP2. Mechanistically, LCD reduced p-p38 MAPK protein expression and inhibited H2O2-induced cell death by regulating the expression of apoptosis-related proteins. These findings confirm that LCD protects against H2O2-induced cytotoxicity, neurotoxicity, and p38 MAPK pathway-related apoptosis by mitigating reactive oxygen species production.